Magnetothermal Multiplexing for Selective Remote Control of Cell Signaling. (10th July 2020) - Moon, Junsang; Christiansen, Michael G.; Rao, Siyuan; Marcus, Colin; Bono, David C.; Rosenfeld, Dekel; Gregurec, Danijela; Varnavides, Georgios; Chiang, Po‐Han; Park, Seongjun; Anikeeva, Polina
Abstract: Magnetic nanoparticles have garnered sustained research interest for their promise in biomedical applications including diagnostic imaging, triggered drug release, cancer hyperthermia, and neural stimulation. Many of these applications make use of heat dissipation by ferrite nanoparticles under alternating magnetic fields, with these fields acting as an externally administered stimulus that is either present or absent, toggling heat dissipation on and off. Here, an extension of this concept, magnetothermal multiplexing is demonstrated, in which exposure to alternating magnetic fields of differing amplitude and frequency can result in selective and independent heating of magnetic nanoparticle ensembles. The differing magnetic coercivity of these particles, empirically characterized by a custom high amplitude alternating current magnetometer, informs the systematic selection of a multiplexed material system. This work culminates in a demonstration of magnetothermal multiplexing for selective remote control of cellular signaling in vitro. Abstract : Magnetothermal multiplexing relies on tuning of alternating magnetic field conditions to magnetic nanoparticle properties to achieve selective heating of distinct ferrofluids. Here, physical modeling, nanomaterials synthesis, and a custom alternating current magnetometer are combined to demonstrate magnetothermal multiplexing in situ and as a means to remotely control two independent cell populations with differing alternating magnetic field conditions.